The Dihydrofolate Reductase 19 bp Polymorphism Is Not Associated with Biomarkers of Folate Status in Healthy Young Adults, Irrespective of Folic Acid Intake. Issue 10 (12th August 2015) - Ozaki, Mari; Molloy, Anne M; Mills, James L; Fan, Ruzong; Wang, Yifan; Gibney, Eileen R; Shane, Barry; Brody, Lawrence C; Parle-McDermott, Anne
Abstract: Background: Dihydrofolate reductase (DHFR) is essential for the conversion of folic acid to active folate needed for one-carbon metabolism. Common genetic variation within DHFR is restricted to the noncoding regions, and previous studies have focused on a 19 bp deletion/insertion polymorphism (rs70991108) within intron 1. Reports of an association between this polymorphism and blood folate biomarker concentrations are conflicting. Objective: In this study, we evaluated whether the DHFR 19 bp deletion/insertion polymorphism affects circulating folate biomarkers in, to our knowledge, the largest cohort to address this question to date. Methods: Healthy young Irish individuals ( n = 2507) between 19 and 36 y of age were recruited between February 2003 and February 2004. Folic acid intake from supplements and fortified foods was assessed with the use of a customized food intake questionnaire. Concentrations of serum folate and vitamin B-12, red blood cell (RBC) folate, and plasma total homocysteine (tHcy) were measured. Data were analyzed with the use of linear regression models. Results: Folic acid intake was positively associated with serum ( P < 0.0001) and RBC ( P = 0.0005) folate concentration and was inversely associated with plasma tHcy ( P = 0.001) as expected. The DHFR 19 bp polymorphism was not significantly associated with either serum ( P = 0.82) or RBC ( P = 0.21) folate, or plasma tHcy ( P = 0.20), even in those within the highest quintile of folic acid intake (>326 μg folic acid/d; P = 0.96). A nonsignificant trend toward lower RBC folate by genotype ( P = 0.09) was observed in the lowest folic acid intake quintile (0–51 μg/d). Conclusion: In this cohort of healthy young individuals, the DHFR 19 bp deletion allele did not significantly affect circulating folate status, irrespective of folic acid intake. Our data rule out a strong functional effect from this polymorphism on blood folate concentrations.